Thermographic assessment of upper body muscles in climbers as a methodology for comparing different skill levels - Comeras-Chueca, C.; Marcen-Cinca, N.; Valero-Campo, C.; Berzosa, C.; Piedrafita, E.; Gutiérrez, H.; Bascuas, P. J.; Bataller-Cervero, A. V. (Frontiers in Sports and Active Living, 2025)
Background: Infrared thermography (IRT) is increasingly used in sports science to monitor muscle temperature changes in athletes. This study aimed to analyze muscle groups of upper body regions warming in climbers, comparing high (HL) and very high-level (VHL) climbers after completing a maximum-difficulty route.